Celastrol ameliorates osteoarthritis via regulating TLR2/NF-κB signaling pathway - Yang, Guangxia; Wang, Kai; Song, Hua; Zhu, Rujie; Ding, Shuai; Yang, Hui; Sun, Jian; Wen, Xin; Sun, Lingyun (Frontiers in Pharmacology, 2022)
Objectives Osteoarthritis (OA) is a joint disease characterized by degeneration of joint cartilage and is a significant cause of severe joint pain, physical disability, and impaired quality of life in the aging population. Celastrol has attracted wide interests for its anti-inflammatory effects on a variety of diseases as a Chinese herbal medicine. This study aimed to investigate the effect of celastrol on OA as well as the mechanisms in vivo and in vitro. Methods A rat knee OA model was established using ‘medial collateral ligament transection (MCLT) + partial meniscectomy (pMMT)’. The OA rats received intra-articular injection of celastrol (1mg/kg) once a week starting from eight weeks after surgery. Safranin O-fast green (S&F) and hematoxylin and eosin (H&E) staining were used to estimate histopathological changes. Micro-CT was used to evaluate bone volume of the subchondral bone of the knee joint. Chondrocytes were isolated from the knee cartilage of rats and OA patients. ELISA, WB, PCR, and IHC were used to detect the expression of inflammatory factors and stromal proteins, respectively. Results We found that celastrol treatment significantly delayed the progression of cartilage damage with a significant reduction in osteophyte formation and bone resorption in OA rat model. In IL-1β-stimulated rat chondrocytes, celastrol significantly suppressed the production of inflammatory factors such as cyclooxygenase-2 (COX2), interleukin-6 (IL-6), and prostaglandin E2 (PEG2), and reduced IL-1β-induced matrix degradation by down-regulating the expression of matrix metalloproteinase 13 (MMP13). In addition, we found that TLR2 was up-regulated in OA patients and rat knee OA models, while celastrol inhibited TLR2 signal and its downstream nuclear factor-κB (NF-κB) phosphorylation. Conclusions In summary, celastrol may improve OA by inhibiting the TLR2/NF-κB signaling pathway, which provides innovative strategies for the treatment of OA.